IMPACT OF ORGANIZATIONAL CLIMATE ON TEACHERS’ JOB SATISFACTION IN PRIVATE SECONDARY SCHOOL - Lhamu, Yuton; Alam, Sahidul (International Journal of Research -GRANTHAALAYAH, 2026)
Job satisfaction of teachers plays a key role in ensuring instructional quality, teacher retention, and overall school effectiveness. In current years, organizational climate has appeared as an important factor of teachers’ professional experiences, mainly in private secondary schools where accountability burdens, performance expectations, and contractual obligations are often intense. This paper presents a conceptual analysis of the organizational climate and teachers’ job satisfaction in private secondary schools. Drawing on a wide review of national and international literature, the study synthesizes key dimensions of organizational climate like leadership style, administrative support, reward systems, working conditions, policy clarity, collegial relations, and resource availability and examines their impact on job satisfaction of teachers. The paper is grounded in established theoretical frameworks such as Herzberg’s Two-Factor Theory, Maslow’s Hierarchy of Needs, Social Exchange Theory, and Self-Efficacy Theory, to explain the mechanisms through which organizational climate shapes teachers’ attitudes and professional commitment. The analysis highlights that a supportive and participative organizational climate enhances teachers’ motivation, psychological well-being, self-efficacy, and job satisfaction, whereas a negative climate contributes to stress, dissatisfaction, and turnover. The study present conceptual understandings and practical suggestions for school leaders and policymakers to foster positive organizational climates that encourage teacher satisfaction and effective school performance.